Suitability of multifunction mobile devices for registration of accounting data of game animals - V. M. Glushkov; Yu. V. Krotov (Аграрная наука Евро-Северо-Востока)
Connection speed, positioning accuracy and stability of the connection with the satellites in any natural landscapes, including forests with high crown closure were determined by the method of comparing the performance of the navigator Garmin GpsMap 62s and GPS-module of smartphone LG. The exact time of communication (7…10 meters) with navigator Garmin GpsMap 62s was 4 minutes. Working positioning accuracy of GPS-module of smartphone LG D325 characterized by the stabilization of the first five digits after the decimal point in the numeric value of the coordinate occurs within 3 minutes after switching on. The magnitude of divergence of positioning points (in pairs) only 4 times exceeded 10 meters two of which (at points 24 and 34) derived from the movement of the operator in place after time when one of the devices point has been already installed. The other 2 (point 11 - 15 m, point 22 - 16.5 m) the reasons for the discrepancies are not establish. Preferential match of center points indicates the presence of both occurring on both devices increase and decrease the error is not related to their parametric data. The study showed a high rate of incorporation and the positioning accuracy of GPS-module of multi-function mobile device that meet the requirement for the routing accounts by any means. In conjunction with the installed function for automatic fast performance recording of the data listed properties of multifunctional mobile devices make it indispensable in conducting census work.